Dermabrasion in a girl with congenital poikiloderma. (Syndrome Rothmund-Thomson) - Periš, Z... (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 1997)
A case of congenital poikiloderma in a 6-year-old girl is reported. The lesions on the face, ears and gluteal area appeared during her first year. Pathohistology of a biopsy taken from the face revealed an atrophic epidermis,dilated capillaries in the papillary dermis and a mild perivascular infiltrate composed of lymphocytes, histiocytes and a few melanophages. A test-dermabrasion was carried out in an area of fully developed lesions on theface. Six months later no lesions could be observed in the dermabraded area, a second biopsy displayed a normal histologic structure of the skin including hair follicules, sebaceous and sweat glands. In view of such observations the author raises the question at what time in the embryonal development do the malformations start in this condition.
Keywords: Child; Dermabrasion; Diagnosis; Pathology; Poikiloderma congenitale; Therapy